A Case of Right Paraduodenal Strangulated Hernia Concomitant with Intestinal Malrotation - Tsuda, Ichiro; Kukita, Kazutaka; Meguro, Zunichi; Sakata, Hiromi; Yonekawa, Motoki; Onodera, Hidetoshi; Yamada, Masahiro; Kawamura, Akio; Kawamata, Futoshi; Tamaki, Tohru (Nippon Shokaki Geka Gakkai zasshi, 2008)
Paraduodenal hernia is a rare etiology of intestinal obstruction that is difficult to diagnose preoperatively and is usually found in surgical exploration. We report a case of a 65-year-old woman with epigastralgia and bilious vomiting, who had a history of open cholecytectomy. Abdominal computed tomography showed dilated intestinal loops posterior to the pancreatic head, which we diagnosed clinically as a small mechanical intestinal obstruction. When conservative treatment with a long intestinal tube was not effective, we conducted emergency surgery on day 3 after admission. Laparotomy showed about 10cm of the ileum to be strangulated by a hernia orifice in the mesenterium near the terminal ileum, and residual incarcerated intestinal loops were located in the retroperitoneal space behind the right mesocolon. This anatomical anomaly without formation of Treitz's ligament yielded a diagnosis of intestinal malrotation concomitant with internal hernia. We expanded the orifice sufficiently and divided the retroperitoneal membrane behind the right mesocolon and coecum, relieving the ileal strangulation and avoiding resection. Intestinal malrotation concomitant with internal hernia is a rare but important cause of bowel obstruction in adults.